PENGARUH UPAH MINIMUM, INVESTASI, DAN PENGELUARAN PEMERINTAH TERHADAP TINGKAT PENGANGGURAN KABUPATEN/KOTA DI PROVINSI BALI - Aryanti, Putu Ayu Leonita; Marhaeni, A.A. I. N (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
The high unemployment rate causes community to be unable maximize their welfare, this case in every area, which is in Bali Province. This study to analyze (1) the simultaneous effect of minimum wages, investment, and government spending on district / municipal unemployment rates Bali Province, (2) the partial effects of minimum wages, investment, and government spending on district / municipal unemployment rates Bali Province, (3) the role of minimum wages in moderating effect of investment and government spending on district / municipal unemployment rate Bali Province. This study uses panel data as 45 observations. The data source in this research is secondary data which comes from the Central Statistics Agency. The analysis technique used is moderated regression analysis. The results of the analysis, (1) Minimum wages, investment, and government spending have a simultaneous effect on the district / municipal unemployment rate Bali Province (2) Minimum wages, investment and government spending have a negative and partially significant effect on the district / municipal unemployment rate cities Bali Province (3) Minimum wage strengthens effect of investment and government the district / municipal unemployment rate Bali Province  Keywords: minimum wage, investment, government spending, unemployment rate